Associations Between Social Support, Social Networks, and Financial Exploitation in Older Adults. (August 2018) - Beach, Scott R.; Schulz, Richard; Sneed, Rodlescia
Social support and social networks are important correlates of elder mistreatment. This study tests hypothesized associations between perceived social support, social network size, and financial exploitation (FE). A population-based survey of 903 older adults (60+) in Allegheny County (Pittsburgh, Pennsylvania) found that lower perceived social support and larger social networks were simultaneously associated with higher risk for FE since age 60, controlling for known risk factors. The same associations were found for FE in the last 6 months. Older adults with larger social networks combined with lower perceived social support were most likely to report FE. When it comes to the role of social relationships and risk for FE, "more may not always be better." Encouragement to widen the social network by "making new friends" should be stressed less than making sure these new network members will truly be supportive of the older adult.